Проблеми та перспективи зовнішньоторговельних відносин України та ЄС - Власенко, Іван Володимирович; Морозова, Наталія Іванівна; Діденко, Олександр; Vlasenko, Ivan; Morozova, Nataliia; Didenko, Oleksandr (Запоріжжя : Видавничий дім «Гельветика», 2026)
UA: Мета полягає у аналізі стану та тенденцій розвитку зовнішньоторговельних відносин України та країн ЄС, визначенні ключових торговельних партнерів і товарних потоків, обґрунтуванні перспективних напрямів поглиблення співпраці. Об'єктом дослідження є зовнішньоторговельні відносини, потоки товарів між Україною та країнами ЄС. У процесі дослідження використовувалися загальнонаукові та спеціальні методи, матеріали Державної служби статистики України. Результати. Встановлено, що ключовим партнером України у зовнішньоторговельній діяльності є країни ЄС. Визначено основних партнерів України за обсягами експорту та імпорту товарів. Проаналізовано структуру експорту. Практична цінність. Дослідження допоможе сфокусувати зусилля на розвитку галузей, які є затребувані на ринку, що дасть можливість бути успішними в конкурентній боротьбі, стане чинником забезпечення економічного розвитку. /// EN: The purpose of the study is to comprehensively analyze the current state, structure and trends in the development of foreign trade relations between Ukraine and the countries of the European Union. Methodology. In the process of research, general scientific and special methods were used: induction and deduction, cause-and-effect relationships, analysis and synthesis; abstract-logical; tabular. Conclusions. Based on the analysis of statistical information on the volumes of exports and imports, it was established that the key partners of Ukraine in foreign trade activities are the EU countries. The main partners of Ukraine in terms of the volumes of exports and imports of goods were identified. It was established that during the studied period, products of plant origin prevailed; fats and oils of animal or plant origin. The main positions of organic product exports were considered. The competitive advantage of organic products is an important component of the competitiveness of the Ukrainian economy. The directions of development of successful cooperation of domestic enterprises with EU countries are determined. It is noted that one of the problems of Ukrainian exports is that a significant share in its structure is represented by raw materials and semi-finished products, that is, products with low added value. Scientific novelty. The scientific article improves the understanding of current trends in international trade between Ukraine and the EU. The idea of promising directions of international trade between Ukraine and the EU has been further developed. Practical value. By analyzing the structure of trade between Ukraine and the EU and understanding its trends, we can focus efforts on the development of industries that are in demand in the market, which will allow us not only to be successful in competition, but also to become a factor in ensuring economic development. Understanding the features and trends in the development of foreign trade relations between Ukraine and the EU will contribute to the formation of new concepts and forecasts, attracting investments, increasing budgets, and developing micro- and macroeconomic processes in the Ukrainian state. Prospects for further research will include consideration of the features of international trade of individual regions of Ukraine with EU countries, taking into account the specifics of the regions and their economic potential.
Problems and prospects of foreign trade relations between ukraine and the EU
Keywords: зовнішньоторговельна діяльність; економічне співробітництво; торговельні партнери; структура експорту; структура імпорту; Європейський ринок; foreign trade activity; economic cooperation; trading partners; export structure; import structure; European market